(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2024)
The advancement of financial technologies has led customers to use digital transactions more and more with the passage of time. With this issue, the share of physical transactions based on cash and coins is decreasing, and more and more people are moving away from traditional payment methods to digital transaction methods. Thus, this study tends to foreground the factors impacting customer’s intention to use digital transactions. This research foregrounds on grasp the control of subjective norms, trust, behavior control, and attitude on the customer’s digital transaction intention. The population of the study was made up of customers and people using electronic transactions on a daily basis. The study adopted a quantitative approach, for which four hundred and four responses were collected through the online questionnaire, and the responses were analyzed using PLS-SEM model approach with Smart PLS 4.0. The exploration of the data concludes that there is a critical positive relation between attitude, perceived behavior control, and usage intention, whereas no significant relation among subjective norms, trust, and usage intention for digital transactions. The implications of this study would benefit to the businessmen, customers, industrialists and organizational leaders to understand the motivation of customers in the trend of digital transaction.